Improving Source Code Encryption using Proposed Cipher Logic - Rasal, SU; Redhu, R; Rasal, VS; Shelar, ST (International Journal of Computer Sciences and Engineering, 2025)
Web page is loaded into web browser to run the required output according to Document Object Model. Web page contents source based on applied technology like language support, platform required and versions used. Indirectly, data can be anything but it is always in the form of 0 and 1. In this paper, proposed cipher logic is applied to the bits data directly due to which it become universal supportive. Five levels proposed cipher logic has been added to the encryption process. Same logic is required to decrypt the encrypted data without which original data cannot be retrieved.